Protein dynamics in living cells studied by in‐cell NMR spectroscopy. Issue 8 (11th January 2013) - Li, Conggang; Liu, Maili
Abstract : Most proteins function in cells where protein concentrations can reach 400 g/l. However, most quantitative studies of protein properties are performed in idealized, dilute conditions. Recently developed in‐cell NMR techniques can provide protein structure and other biophysical properties inside living cells at atomic resolution. Here we review how protein dynamics, including global and internal motions have been characterized by in‐cell NMR, and then discuss the remaining challenges and future directions.